Attitudes of patients and surgeons towards sham surgery trials: a protocol for a scoping review of attributes to inform a discrete choice experiment. Issue 3 (10th March 2020) - Wall, Laura; Hinwood, Madeleine; Lang, Danielle; Smith, Angela; Bunzli, Samantha; Clarke, Philip; Choong, Peter F M; Dowsey, Michelle M; Paolucci, Francesco
Abstract : Introduction: In order to properly evaluate the efficacy of orthopaedic procedures, rigorous, randomised controlled sham surgery trial designs are necessary. However, randomised controlled trials (RCTs) for surgery involving a placebo are ethically debated and difficult to conduct with many failing to reach their desired sample size and power. A review of the literature on barriers and enablers to recruitment, and patient and surgeon attitudes and preferences towards sham surgery trials, will help to determine the characteristics necessary for successful recruitment. Methods and analysis: This review will scope the diverse literature surrounding sham surgery trials with the aim of informing a discrete choice experiment to empirically test patient and surgeon preferences for different sham surgery trial designs. The scoping review will be conducted in accordance with the methodological framework described in Arksey and O'Malley (2005) and reported using the Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocols extension for Scoping Reviews. The review will be informed by a systematic search of Medline, Embase, PsycInfo, CINAHL and EconLit databases (from database inception to 21 June 2019), a Google Scholar search, and hand searching of reference lists of relevant studies or reviews. Studies or opinion pieces that involve patient, surgeon or trial characteristics, which influence the decision to participate in a trial, will be included. Study selection will be carried out independently by two authors with discrepancies resolved by consensus among three authors. Data will be charted using a standardised form, and results tabulated and narratively summarised with reference to the research questions of the review. Ethics and dissemination: The findings from this review will inform the design of a discrete choice experiment around willingness to participate in surgical trials, the outcomes of which can inform decision and cost-effectiveness models of sham surgery RCTs. The qualitative information from this review will also inform patient-centred outcomes research. The review will be published in a peer-reviewed journal. Trial registration number: CRD42019133296.